A EJA na escola Raimundo Nunes: disparidade da SEMED ao chão da escola - GOES, Ediane Maia (2021)
This work has as its theme the modality of teaching EJA - Education of Young people and adults making a relationship between the municipal education secretariat of the municipality of Acará with the school reality faced by the students and teachers of this teaching, the research was held at raimundo nunes school located in rural space, in PA 252 km 14 called the Cravo Community and also in the municipal department of education that is located at the city's headquarters, it aims to understand the process of schooling young people and adults in this territory. The research is qualitative in nature, the data collection process occurred through semi-structured interviews with scripts previously formulated with the coordinator and technique responsible for the general coordination of the EJA in the municipality and, participant observation in the school already mentioned. The data were analyzed from renowned theorists in the area of education of young people and adults such as Freire, Gadotti, Paiva, Santos and others who contributed to the process. Therefore, after the analysis of the data obtained it is understood that the process of schooling of young people and adults in the municipality of Acará, is still neglected by the public authorities. The work aims to promote a reflection of how this modality of teaching has been treated so that it can promote changes about the decisions taken by which they imply in society.